INVESTIGASI KUALITAS UDARA RUANG PERKULIAHAN DI KOTA BANDUNG MENGGUNAKAN VENTILASI PASIF - Rosulindo, Parisya Premiera; Prasetyo, Bowo Yuli (P3M Politeknik Negeri Indramayu, 2025)
Indoor air quality has become a critical concern due to its significant impact on human health, as 80%-90% of human activities are conducted indoorsThis study aims to assess the air quality in a university classroom in Bandung City that utilizes passive ventilation, focusing on CO₂ concentration, temperature, and humidity parameters. A quantitative approach involving observational and experimental methods was employed by varying the opening levels of passive ventilation into three conditions: fully open, half-open, and fully closed. The results indicate that fully open ventilation effectively maintains good air quality with stable CO₂ concentration, temperature, and humidity. Conversely, under fully closed ventilation conditions, there is a significant increase in CO₂ concentration, temperature, and humidity, which can reduce comfort and pose health risks.The findings emphasize the importance of managing passive ventilation to ensure a healthy and comfortable classroom environment.